Entrepreneurial determinants of Moroccan business failure: entrepreneurial behaviors and attitudes - Zizi, Youssef; Jamali-Alaoui, Amine; El Goumi, Badreddine (Business: Theory and Practice, 2025)
The main objective of this article is to determine the entrepreneurial determinants of Moroccan business failures. To address our research problem, we employ multiple regression models. Entrepreneurial behaviors and attitudes are sourced from the dataset provided by Global Entrepreneurship Monitor (GEM). Additionally, we enhance our dataset by incorporating entrepreneurial variables from the World Bank entrepreneurship database and OMPIC. Applying variable selection techniques and models selection criteria, such as AIC and BIC, the main results indicate that the model composed of variables related to entrepreneurial behavior and attitudes variables, specifically fear of failure rate, perceived capabilities rate, and perceived opportunities rate, better explains bankruptcy rate. This empirical study represents the inaugural examination in Morocco employing entrepreneurial behaviors and attitudes variables to assess their impact on business failure. The findings from this article could open up new perspectives for identifying entrepreneurial variables that explain business failure in Morocco. To the best of our knowledge, our research is the first to explore this topic in this country.